Moral Education Through Minangkabau Oral Tradition: A Semiotic Analysis of ‘Budi’ Pantun in the Context of Cultural Preservation - Wulandari, Yosi; Rahmah, Fauziah (Universitas PGRI Sumatera Barat, 2025)
In the face of rapid globalization, traditional oral literature faces the risk of marginalization, particularly in its role as a transmitter of local wisdom and moral values. This study examines the Minangkabau traditional pantun titled Budi to explore how moral education is embedded within local poetic forms. Utilizing Riffaterre’s semiotic framework, the research applies qualitative referential analysis to uncover the symbolic and intertextual dimensions of the text. Data were collected through observation and note-taking, followed by a four-stage semiotic reading process: heuristic reading, hermeneutic interpretation, matrix-model-variant analysis, and intertextual mapping. The findings reveal that Budi pantun encapsulates a rich tapestry of moral teachings: heuristic reading uncovers normative guidance for proper conduct; hermeneutic reading highlights deeper ethical reflections; matrix-model-variant analysis emphasizes cultural ideals of civility; and intertextual analysis connects the pantun with broader moral discourses in Minangkabau and Nusantara traditions. This research contributes to the preservation of intangible cultural heritage by documenting and analyzing indigenous moral philosophy embedded in oral literature. It also provides a critical pedagogical framework for integrating traditional texts into character education curricula. By highlighting the educational potential of pantun, the study advocates for culturally responsive teaching strategies that reinforce local identity while fostering universal ethical values. Future research should explore comparative semiotic analyses across ethnic literary traditions to enrich intercultural understanding and moral literacy in education systems.